Relationships between antibiotic exposure and asthma in adults in the United States: results of the National Health and Nutrition Examination Survey between 1999 and 2018 - Shaoli Li; Feilong Chen; Chunlei Huang; Guimin Huang; Yijing Cheng; Tao Li; Dongqing Hou; Wenqian Liu; Tao Xu; Junting Liu (Frontiers Media S.A., 2023)
ObjectivesTo investigate the relationship between antibiotic exposure and asthma in adults in the United States.MethodsData was obtained from the National Health and Nutrition Examination Survey (NHANES) conducted between 1999 and 2018. A total of 51,124 participants were included, excluding those who were aged < 20 years, female participants who were pregnant, and individuals who did not complete the prescription medications questionnaire and the medical conditions questionnaire regarding asthma status. Antibiotic exposure was defined as the utilization of antibiotics within the past 30 days, categorized based on the Multum Lexicon Plus therapeutic classification system. Asthma was defined as having a history of asthma or having an asthma attack or wheezing symptoms in the past year.ResultsThe risk of asthma was found to be 2.557 (95% CI: 1.811, 3.612), 1.547 (95% CI: 1.190, 2.011) and 2.053 (95% CI: 1.344, 3.137) times greater in participants who had used macrolide derivatives, penicillin and quinolones in the past 30 days, respectively, compared with those not using antibiotics. After adjusting for demographic covariates and asthma-related factors, only macrolides derivatives were significantly associated with asthma in the 20-40 and 40-60 age groups. For individuals over 60 years old, quinolones were significantly associated with asthma. The effect of different types of antibiotic with asthma varied in male and female populations. Moreover, higher socioeconomic status, greater BMI, younger age, smoking habits, history of infection, chronic bronchitis, emphysema, and family history of asthma were all identified as risk factors for asthma.ConclusionOur study indicated that three types of antibiotics were significantly associated with asthma in different subgroups of the population. Therefore, the use of antibiotics should be more strictly regulated.